Method for preparing high-coating-property silver-coated copper powder by utilizing nano copper powder and application of high-coating-property silver-coated copper powder
By performing acid treatment and silver salt deposition on nanocopper powder, the problem of poor coating of silver-clad copper powder at the nanoscale is solved, and high-quality preparation of silver-clad copper powder is achieved, which improves the conductivity and oxidation resistance. It is suitable for for solar cell applications.
Patent Information
- Application Number
- CN202411524741.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing preparation methods for silver-clad copper powder have poor cladding properties at the nanoscale, resulting in reduced conductivity and poor oxidation, making it difficult to achieve large-scale production of high-quality nano-clad copper powder materials.
Using nanocopper powder as the substrate, the oxide layer is removed through an acid solution, the deionized water and a replacement solvent are used for stirring, the silver salt solution is slowly added, centrifuged and washed multiple times, and finally dried in the oven, the temperature and stirring conditions are controlled. , optimize the formation of silver cladding.
提高了银包铜粉的抗氧化性和导电性能,降低了生产成本,实现了高包覆性银包铜粉的制备,适用于太阳能电池浆料,延长了材料的稳定性和使用寿命。
Smart Images

Figure CN119216575A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal powders, and in particular relates to a method for preparing high-coating silver-coated copper powder by utilizing nano copper powder and application thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasingly prominent environmental problems, photovoltaic power generation is gradually becoming the mainstream as a clean, sustainable and pollution-free form of energy. The metal conductive layer in solar cells is one of the key components of solar cells. Its preparation material, indium tin oxide (ITO), is scarce and expensive. It is easily damaged in flexible solar cells, affecting its stability. Therefore, the development of new low-cost materials is of great significance to the development of the photovoltaic industry.
[0003] Nanosilver has significant advantages in improving light absorption and carrier separation efficiency due to its excellent optical, electrical and thermal properties, and has great application potential in the photovoltaic field. However, silver is expensive, and the silver migration problem also restricts its industrialization process. Nano copper powder has similar conductivity to silver and is cheaper, but it is easier to oxidize than silver. Therefore, coating the surface of copper powder with silver can not only improve the oxidizability of copper but also effectively solve the silver migration problem.
[0004] At present, the silver-coated copper powder processes that have been publicly reported mainly include melt atomization, mechanical ball milling and chemical reduction. The spray pyrolysis coating process is difficult to control and the equipment investment is high. The mechanical ball milling method is limited to the preparation of flaky silver-coated copper powder and has high energy consumption. The chemical reduction method is the most commonly used method for silver-coated copper, but this process method is only applicable to the preparation of silver-coated copper powder above the micron scale. There are still many bottlenecks at the nanoscale level. In detail, as the particle size decreases, the encapsulation of the manufactured product will decrease, which will lead to partial oxidation in the subsequent process and the decrease of conductivity in the final application. Therefore, this project aims to invent an in-situ replacement deposition technology and realize the large-scale production of high-quality nano silver-coated copper powder materials based on this technology, so as to solve the challenges faced by nano metal materials for photovoltaics. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing high-coating silver-coated copper powder using nano-copper powder and its application in order to solve the problem that the final product obtained by the existing silver-coated copper powder preparation method has poor coating and easily leads to partial oxidation of the product during subsequent use.
[0006] The present invention achieves the above-mentioned purpose through the following technical scheme: A method for preparing high-coating silver-coated copper powder using nano copper powder comprises the following steps:
[0007] S01, preparing reactants: providing nano copper powder, wherein the particle size of the nano copper powder is 20-80 nm;
[0008] Providing an acidic solution, wherein the acidic solution includes any one of dilute sulfuric acid, hydrochloric acid or citric acid or a combination of at least two thereof;
[0009] Providing deionized water, wherein the conductivity of the deionized water is 0.1-10 μS / cm;
[0010] providing a displacement solvent, wherein the displacement solvent includes any one or a combination of butyl carbitol or glycerol;
[0011] Providing a silver salt solution, wherein the silver salt solution comprises an aqueous solution of any one of silver nitrate, silver ammonia or a silver complex, or a combination of at least two thereof;
[0012] S02, reaction step: placing the nano copper powder into an acidic solution to remove the oxide layer on the surface of the copper powder, and then washing away the acidic solution remaining on the surface of the copper powder with the deionized water;
[0013] Adding the treated nano copper powder to the displacement solvent at a stirring speed of 100-200 rpm for 6-8 min to ensure that the nano copper powder is completely dispersed;
[0014] Slowly add the silver salt solution during stirring, keep the stirring speed at 100-200 rpm, and the stirring reaction time is 5-7 minutes;
[0015] S03, subsequent treatment step: the mixed solution after the reaction in step S02 is allowed to stand for 1-2 hours;
[0016] A centrifuge is used for solid-liquid separation, and the centrifuge is centrifuged at a speed of 2000-3000 rpm for 10-12 minutes to separate the precipitate;
[0017] Wash the precipitate with the deionized water for 2-3 times, each washing time being 5-8 minutes, to remove the unreacted replacement solvent and the silver salt solution;
[0018] The washed precipitate is dried in an oven at 50-60° C. for 2-3 h to obtain the final silver-coated copper powder.
[0019] Furthermore, the mass ratio of the nano copper powder, the replacement solvent and the silver salt solution is 1:(4-6):(0.1-0.5).
[0020] Furthermore, the concentration of the acidic solution is 0.1-1 mol / L.
[0021] Furthermore, the temperature of the reaction stirring process in step S02 is maintained at 10-50°C.
[0022] The high-coating silver-coated copper powder prepared by the method is used in solar cell slurry.
[0023] Beneficial effects: The invention has reasonable design, simple and stable structure, strong practicability, and has the following advantages:
[0024] 1. Enhanced oxidation resistance: The silver coating effectively prevents the oxidation of nano copper powder, prolongs the stability and service life of the material in the air, thereby improving the reliability of the product;
[0025] 2. Reduce production costs: Using nano copper powder as the base material can reduce costs while maintaining good electrical conductivity and has a high cost-effectiveness;
[0026] 3. Improve electrical conductivity: The present invention can control the thickness of the silver plating layer and the size of the silver-coated copper particles by adjusting the particle size of the copper particles and the mass fraction of silver. The silver-coated copper powder maintains good fluidity and the hidden layer coating is uniform and dense, and silver-coated copper particles with excellent electrical conductivity, thermal conductivity and corrosion resistance can be obtained;
[0027] 4. Optimization of overall performance: The present invention adopts in-situ replacement deposition technology to make free silver ions preferentially undergo replacement reduction reaction on the surface of nano-copper to form a uniform and dense silver coating;
[0028] 5. Simple operation process: no need to adjust parameters such as pH value, fewer steps, low energy consumption, and improved process flexibility and adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the structure of the silver-coated copper powder under a microscope according to Example 1 of the present invention;
[0030] Figure 2 This is a schematic diagram of the structure of the silver-coated copper powder under microscopy in Example 2 of the present invention;
[0031] Figure 3 The diameter test data of the silver-coated copper powder in Example 2 of the present invention;
[0032] Figure 4 This is a schematic diagram of the structure of the silver-coated copper powder under a microscope of Example 3 of the present invention;
[0033] Figure 5 This is the test data of the diameter of the silver-coated copper powder in Example 3 of the present invention;
[0034] Figure 6 The particle size data of the silver-coated copper powder obtained by laser particle size analyzer analysis in Example 3 of the present invention;
[0035] Figure 7 This is a display image of silver-coated copper powder under high-resolution TEM of Example 3 of the present invention. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0037] Embodiment 1:
[0038] A method for preparing high-coating silver-coated copper powder using nano copper powder comprises the following steps:
[0039] S01. Prepare reactants: Provide nano copper powder, the particle size of which is 20 nm. This ultrafine particle has a high specific surface area and good reactivity, ensuring its uniform morphology, thereby improving the efficiency of subsequent reactions;
[0040] Providing an acidic solution, the acidic solution includes any one of dilute sulfuric acid, hydrochloric acid or citric acid or a combination of at least two of them. These acids can effectively remove the oxide layer on the surface of the nano copper powder to ensure a more uniform deposition of silver. Dilute sulfuric acid helps to form stable copper ions, while hydrochloric acid can help dissolve other impurities. Citric acid can not only remove oxides, but also serve as a complexing agent in subsequent reactions to help stabilize metal ions.
[0041] Deionized water is provided. The conductivity of deionized water is 0.1 μS / cm, which means that it has high purity and contains very few ions. Deionized water is used to wash the nano copper powder to avoid the influence of impurities on the reaction and ensure the smooth progress of subsequent reactions and the purity of the final product.
[0042] Providing a replacement solvent, the replacement solvent includes any one or a combination of butyl carbitol or glycerol, these solvents have good solubility and suitable volatility, can effectively dissolve silver salts, and play a stabilizing role in the subsequent silver ion deposition process. Selecting a suitable replacement solvent can improve the coating property of the silver-coated copper powder;
[0043] Providing a silver salt solution, the silver salt solution includes any one of silver nitrate, silver ammonia or a silver complex, or a combined aqueous solution of at least two of them, these silver salts provide silver ions as a deposition source, silver nitrate is a commonly used silver source, and silver ammonia can increase the solubility of silver, thereby promoting the deposition of silver, and selecting a suitable silver salt can improve the efficiency and uniformity of silver coating;
[0044] S02, reaction step: placing the nano copper powder in an acidic solution to remove the oxide layer on the surface of the copper powder. This step is crucial because the presence of the oxide layer will hinder the deposition of silver, resulting in a decrease in the quality of the final product. Then, the acid solution remaining on the surface of the copper powder is washed away with deionized water. The cleaning process needs to be thorough. Ultrasonic cleaning or multiple rinses can be used during the process to ensure that there is no residue of the acid solution, thereby avoiding affecting the subsequent reaction.
[0045] The treated nano copper powder was added to the displacement solvent at a stirring speed of 100 rpm for 6 min to ensure that the nano copper powder was completely dispersed to form a uniform dispersion. Effective dispersion facilitates the subsequent uniform deposition of silver salt and improves the uniformity of silver coating.
[0046] Slowly add the silver salt solution during the stirring process, keep the stirring speed at 100 rpm, and the stirring reaction time is 5 minutes. In this step, silver ions are deposited on the surface of the nano copper powder to form a silver coating layer. Slowly adding the silver salt solution can control the reaction rate, avoid excessive deposition and agglomeration of silver, and ensure uniform coating;
[0047] S03, subsequent treatment step: the mixed solution after the reaction in step S02 is allowed to stand for 1 hour. This process allows the unprecipitated silver ions to continue to react with the copper powder to form a more stable silver-coated copper powder;
[0048] A centrifuge is used for solid-liquid separation. The centrifuge is centrifuged at a speed of 2000 rpm for 10 minutes to separate the precipitate. This step can effectively separate the precipitate and the supernatant, and collect the silver-coated copper powder in the precipitate. The appropriate centrifugal speed and time can ensure that most of the precipitate is collected while reducing the residual solution;
[0049] The precipitate was washed twice with deionized water, each washing time was 5 minutes, to remove the unreacted replacement solvent and silver salt solution. Thorough washing can improve the purity of the final product and avoid the influence of impurities on subsequent applications;
[0050] The washed precipitate is dried in an oven at 50°C for 2 hours to obtain the final silver-coated copper powder. The appropriate drying temperature and time can ensure that the silver-coated copper powder maintains good morphology and performance, avoids the reduction or decomposition of silver due to excessively high temperature, and ensures that high-quality silver-coated copper powder is finally obtained.
[0051] Among them, in the overall preparation method, the mass ratio between nano copper powder, displacement solvent and silver salt solution is 1:4:0.1. The selection of this ratio means that every 1 gram of nano copper powder corresponds to 4 grams of displacement solvent and 0.1 gram of silver salt solution, which helps to maintain the balance of the reaction and optimize the silver loading. The concentration of the acidic solution is 0.1 mol / L, which indicates that the acid content in the solution is moderate, which helps to improve the reaction rate and efficiency, while avoiding the potential corrosion of the nano copper powder by an overly strong acidic environment. The temperature of the reaction stirring process in step S02 is maintained at 10°C. At this temperature, the molecular movement of the reactants is slower, which is conducive to forming a uniform reaction environment and reducing the probability of side reactions. In addition, lower temperatures also help to control the growth rate of nanoparticles, thereby achieving refinement and homogenization of nanoparticles. This meticulous temperature control and component ratio design have an important influence on the morphology, structure and performance of the final product.
[0052] The microstructure of the silver-coated copper powder prepared by the above method is as follows: Figure 1 As shown, silver-coated copper nanopowder with a silver content of 10% was obtained. The nano silver-coated copper powder was spherical in shape with an average diameter of 30 nm. Its conductivity was tested by a four-probe method. The average value taken at 30 MPa was 9823 S / cm, and it was used in solar cell slurry.
[0053] Embodiment 2:
[0054] A method for preparing high-coating silver-coated copper powder using nano copper powder comprises the following steps:
[0055] S01. Prepare reactants: provide nano copper powder, the particle size of the nano copper powder is 55 nm;
[0056] Providing an acidic solution, the acidic solution comprising any one of dilute sulfuric acid, hydrochloric acid or citric acid or a combination of at least two thereof;
[0057] Deionized water was provided, and the conductivity of the deionized water was 5 μS / cm;
[0058] Providing a displacement solvent, the displacement solvent comprising any one or a combination of butyl carbitol or glycerol;
[0059] Providing a silver salt solution, the silver salt solution comprising an aqueous solution of any one of silver nitrate, silver ammonia or a silver complex, or a combination of at least two thereof;
[0060] S02, reaction step: placing the nano copper powder into an acidic solution to remove the oxide layer on the surface of the copper powder, and then washing away the acidic solution remaining on the surface of the copper powder with deionized water;
[0061] The treated nano copper powder was added to the displacement solvent at a stirring speed of 150 rpm for 7 min to ensure that the nano copper powder was completely dispersed;
[0062] The silver salt solution was slowly added during the stirring process, the stirring speed was maintained at 150 rpm, and the stirring reaction time was 6 min;
[0063] S03, subsequent treatment step: the mixed solution after the reaction in step S02 is allowed to stand for 1.5 hours;
[0064] The solid-liquid separation was performed using a centrifuge at 2500 rpm for 11 min to separate the precipitate;
[0065] The precipitate was washed with deionized water for 3 times, each washing time was 6 min, to remove the unreacted replacement solvent and silver salt solution;
[0066] The washed precipitate was dried in an oven at 55°C for 2.5 h to obtain the final silver-coated copper powder.
[0067] In the overall preparation method, the mass ratio of nano copper powder, replacement solvent and silver salt solution is 1:5:0.3, the concentration of the acidic solution is 0.5 mol / L, and the temperature of the reaction stirring process in step S02 is maintained at 25°C.
[0068] The microstructure of the silver-coated copper powder prepared by the above method is as follows: Figure 2 As shown in FIG. 1 , a silver-coated copper nanopowder with a silver content of 30% was obtained. The nano silver-coated copper powder was spherical in shape with an average diameter of 72 nm. Figure 3 As shown, the conductivity is tested to be 14792S / cm.
[0069] Embodiment three:
[0070] A method for preparing high-coating silver-coated copper powder using nano copper powder comprises the following steps:
[0071] S01. Prepare reactants: provide nano copper powder, the particle size of which is 80 nm;
[0072] Providing an acidic solution, the acidic solution comprising any one of dilute sulfuric acid, hydrochloric acid or citric acid or a combination of at least two thereof;
[0073] Deionized water was provided, and the conductivity of the deionized water was 10 μS / cm;
[0074] Providing a displacement solvent, the displacement solvent comprising any one or a combination of butyl carbitol or glycerol;
[0075] Providing a silver salt solution, the silver salt solution comprising an aqueous solution of any one of silver nitrate, silver ammonia or a silver complex, or a combination of at least two thereof;
[0076] S02, reaction step: placing the nano copper powder into an acidic solution to remove the oxide layer on the surface of the copper powder, and then washing away the acidic solution remaining on the surface of the copper powder with deionized water;
[0077] The treated nano copper powder was added to the displacement solvent with a stirring speed of 200 rpm and a stirring time of 8 min to ensure that the nano copper powder was completely dispersed;
[0078] Slowly add the silver salt solution during stirring, keep the stirring speed at 200 rpm, and stir for 7 min;
[0079] S03, subsequent treatment step: the mixed solution after the reaction in step S02 is allowed to stand for 2 hours;
[0080] The solid-liquid separation was performed using a centrifuge at 3000 rpm for 12 min to separate the precipitate;
[0081] The precipitate was washed with deionized water for 3 times, each washing time was 8 min, to remove the unreacted replacement solvent and silver salt solution;
[0082] The washed precipitate was dried in an oven at 60°C for 3 h to obtain the final silver-coated copper powder.
[0083] In the overall preparation method, the mass ratio of nano copper powder, replacement solvent and silver salt solution is 1:6:0.5, the concentration of the acidic solution is 1 mol / L, and the temperature of the reaction stirring process in step S02 is maintained at 50°C.
[0084] The microstructure of the silver-coated copper powder prepared by the above method is as follows: Figure 4 As shown in FIG. 1 , a silver-coated copper nanopowder with a silver content of 50% was obtained. The nano silver-coated copper powder was spherical in shape with an average diameter of 93 nm. Figure 5-6 As shown, the conductivity is 15400 S / cm. In addition, high-resolution TEM shows that the surface of the copper particles is evenly coated with a layer of silver. Figure 7 shown.
[0085] Example 4: Comparison of specific parameters and performance of silver-coated copper powder prepared by the methods of Examples 1 to 3
[0086] The specific results are as follows:
[0087] parameter Embodiment 1 Embodiment 2 Embodiment 3 Nano copper powder particle size 20nm 55nm 80nm Silver content 10% 30% 50% Conductivity 9823 S / cm 14792 S / cm 15400 S / cm Coating form Spherical Spherical Spherical Average diameter of silver-coated copper powder 30nm 72nm 93nm Acid solution concentration 0.1mol / L 0.5mol / L 1mol / L Replacement solvent ratio 1:4:0.1 1:5:0.3 1:6:0.5 Reaction stirring time 10℃ 25℃ 50℃ Standing time 1h 1.5h 2h Applied to solar cell paste yes yes yes
[0088] Analyze and discuss the above table:
[0089] 1. Nano copper powder particle size:
[0090] The nano copper powder of Example 1 has the smallest particle size (20 nm), which may result in the largest specific surface area, which helps to improve the reaction rate and silver deposition efficiency. However, due to the small particle size, there may be a risk of aggregation during operation and application.
[0091] The nano copper powders of Examples 2 and 3 have larger particle sizes (55 nm and 80 nm), and although they have smaller specific surface areas, they are easier to control and process in some cases.
[0092] 2. Silver content of silver coating layer:
[0093] Embodiment 3 has the highest silver content (50%), and it is expected that its conductivity and conducting properties will be the best among all embodiments, and is suitable for applications with high conductivity requirements, such as solar cells;
[0094] The silver content of Example 1 is the lowest (10%). Although the conductivity is relatively high, the silver content may limit its application in high-efficiency batteries.
[0095] 3. Conductivity:
[0096] Example 3 has the highest conductivity (15400 S / cm), which makes it an ideal choice for solar cell paste, providing better conductivity;
[0097] The conductivity of Example 2 is also very high (14792 S / cm), and is also suitable for high-performance battery applications.
[0098] 4. Stirring speed and time:
[0099] The stirring speed of Example 1 was the lowest (100 rpm), while the stirring speed of Example 3 was the highest (200 rpm), which may affect the deposition rate and uniformity of silver ions. A higher stirring speed generally contributes to more uniform dispersion and deposition.
[0100] 5. Drying process:
[0101] As the drying temperature increases (50° C. in Example 1 and 60° C. in Example 3), silver may be reduced or decomposed, so it is very important to control the drying conditions.
[0102] Summarize:
[0103] Embodiment 1: Suitable for applications that do not require high silver content, moderate conductivity, and suitable for solar cell pastes of general performance;
[0104] Example 2: The conductivity is relatively high, the silver content is moderate, and it is suitable for solar cell pastes requiring slightly higher performance;
[0105] Embodiment 3: The best choice, with the highest silver content and conductivity, suitable for high-performance solar cell paste;
[0106] This table helps to clearly compare the key parameters between different embodiments, facilitates the analysis of their application potential in solar cell pastes, and according to specific application requirements, a suitable embodiment can be selected for further optimization and adjustment.
[0107] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and range of equivalents of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0108] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing high-coating silver-coated copper powder using nano copper powder, characterized in that , including the following steps: S01, preparing reactants: providing nano copper powder, wherein the particle size of the nano copper powder is 20-80 nm; Providing an acidic solution, wherein the acidic solution includes any one of dilute sulfuric acid, hydrochloric acid or citric acid or a combination of at least two thereof; Providing deionized water, wherein the conductivity of the deionized water is 0.1-10 μS / cm; providing a displacement solvent, wherein the displacement solvent includes any one or a combination of butyl carbitol or glycerol; Providing a silver salt solution, wherein the silver salt solution comprises an aqueous solution of any one of silver nitrate, silver ammonia or a silver complex, or a combination of at least two thereof; S02, reaction step: placing the nano copper powder into an acidic solution to remove the oxide layer on the surface of the copper powder, and then washing away the acidic solution remaining on the surface of the copper powder with the deionized water; Adding the treated nano copper powder to the displacement solvent at a stirring speed of 100-200 rpm for 6-8 min to ensure that the nano copper powder is completely dispersed; Slowly add the silver salt solution during stirring, keep the stirring speed at 100-200 rpm, and the stirring reaction time is 5-7 minutes; S03, subsequent treatment step: the mixed solution after the reaction in step S02 is allowed to stand for 1-2 hours; A centrifuge is used for solid-liquid separation, and the centrifuge is centrifuged at a speed of 2000-3000 rpm for 10-12 minutes to separate the precipitate; Wash the precipitate with the deionized water for 2-3 times, each washing time being 5-8 minutes, to remove the unreacted replacement solvent and the silver salt solution; The washed precipitate is dried in an oven at 50-60° C. for 2-3 h to obtain the final silver-coated copper powder.
2. The method for preparing high-coating silver-coated copper powder using nano copper powder according to claim 1, characterized in that: The mass ratio of the nano copper powder, the replacement solvent and the silver salt solution is 1:(4-6):(0.1-0.5).
3. The method for preparing high-coating silver-coated copper powder using nano copper powder according to claim 2, characterized in that: The concentration of the acidic solution is 0.1-1 mol / L.
4. The method for preparing high-coating silver-coated copper powder using nano copper powder according to claim 3, characterized in that: The temperature of the reaction stirring process in step S02 is maintained at 10-50°C.
5. The use of the high-coating silver-coated copper powder prepared by the method according to any one of claims 1 to 4, characterized in that: The prepared silver-coated copper powder is used in solar cell slurry.
